Waldheims Walzer - Beckermann, Ruth; Beckermann, Ruth; Hennrich, Kurt; Beckermann, Ruth; Grandpierre, Manuel; Pototschnig, Rudi (Austria : ELF Pictures, 2018)
“Waldheim no, Waldheim no” shouts a crowd in the center of Vienna in 1986. Ruth Beckermann was one of the activists trying to prevent the election of Kurt Waldheim, and documented the political events with her camera. More than 30 years later, she revisits her archive and uses additional material to analyze this turning point in Austrian political culture. The film shows the web in which former UN Secretary General Kurt Waldheim became ensnared by concealing two years of his wartime biography. It analyses the collapse of the Austrian grand illusion: having been the first victim of the Nazis.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films